EMOTIONAL REGULATION MEDIATING SOCIAL ANXIETY AND PSYCHOLOGICAL WELL-BEING EFFECTS ON MENTAL HEALTH - Ramadhi Ramadhi; Kiki Sarianti; Desi Rosalina; Khairul Ikhwan; Riko Erlima (LPPM STIE Muhammadiah Bandung, 2026)
The rapid digitalization of work environments and increasing performance demands have intensified psychological pressures among Generation Z employees, making them particularly vulnerable to social anxiety, emotional dysregulation, and declining mental health. Despite growing attention to workplace mental health, limited empirical evidence explains the psychological mechanisms through which social anxiety and psychological well-being shape mental health outcomes among young workers, especially in developing urban contexts. This study examines the influence of Social Anxiety and Psychological Well-Being on Mental Health through Emotional Regulation among Generation Z workers in Padang City, Indonesia. The research aims to investigate both the direct and indirect relationships between these psychological variables. A quantitative approach within a positivist paradigm was applied, involving 120 employees across service, retail, hospitality, and administrative sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both measurement and structural models. The findings reveal that Social Anxiety negatively affects Emotional Regulation and Mental Health, while Psychological Well-Being positively influences both constructs. Emotional Regulation significantly impacts Mental Health and partially mediates the effects of Social Anxiety and Psychological Well-Being on Mental Health. These results underscore the critical role of Emotional Regulation as a psychological mechanism that mitigates the adverse effects of Social Anxiety and strengthens the protective function of Psychological Well-Being. Practically, organizations are encouraged to implement interventions such as emotional intelligence training, mindfulness practices, and stress management programs to enhance emotional regulation capacities and support the mental health of Generation Z employees.